Can enantiomer ligands produce structurally distinct homochiral MOFs? - Dubey, Mrigendra; Kumar, Ashish; Dhavale, Vishal M.; Kurungot, Sreekumar; Pandey, Daya Shankar (CrystEngComm, 2015)
Here, we report a self-assembled homochiral metal-organic framework [Cu-1.5(H2LL-leu)(Ac)H2O](n)center dot 3H(2)O (1) obtained from an L-leucine-derived ligand (H4L(L-leu)) and Cu(Ac)(2)center dot H2O in a 1 : 1 ratio. Coordination-induced conformational change in the ligand has been monitored by circular dichroism which has been further attested by synthesizing a D-leucine-containing enantiomer H4L D-leu and its Cu(II) complex [Cu-1.5(H2LD-leu)H2O](n)center dot 10H(2)O (2). Structure determination revealed entirely different structures for the homochiral MOFs (1 and 2) obtained from the L/D-leucine-derived enantiomer ligands under analogous reaction conditions. Further, structural dissimilarity in these MOFs has been judicially supported by proton conductance studies. MOF 1 shows higher proton (10(-5) S cm(-1)) conductance in comparison to 2 (10(-6) S cm(-1)) due to dissimilar alignment of the hydrogen-bonded water molecules in the hydrophilic pocket as well as crystal packing.